Technological solution for excavating the returnable coal zone at the "Gacko" power plant for the purpose of improving the heat value of the energy fuel for the Gacko power plant - Vuković Boško (Bakar)
Due to the movement of blocks on the overburden and coal, on the southern slope of field "C", where the main coal layer, with optimal quality characteristics, was exploited as fuel for TE Gacko, the exploitation of coal in the Central exploitation zone was completely suspended. Coal supply for the Gacko thermal power plant, from April 2024, is made exclusively from roof coal seams. The upper strip level (12 Ng) is represented by the increased participation of tailings in the coal layer with coal interlayers of small thickness, whose exploitation is difficult with mining machinery, due to the low coefficient of utilization of exploitation reserves. Smaller layers of coal are separated by packages of stratified tailings of greater thickness, so the exploitation of these coal reserves would be necessary for a longer period and would not provide continuity in the safe supply of energy fuel to the thermal power plant. The only variant of using the coal reserves of the upper belt level is in combination with the middle coal layer in the deep layer, with a high degree of availability of mining machinery. For the calculation of coal reserves of the upper belt level, all strata that meet the heat value of the thermal power plant were taken collectively, and coal strata of low calorific value were excluded because they create negative effects during combustion in the boiler of the thermal power plant (increased slag and ash).